Annual report 2012 - (UN New YorkUS, 2013)
Focuses on indicators of physical, economic and decision-making autonomy as seen against the backdrop of the regional agenda shaped by the consensuses reached at the ninth session of the Regional Conference on Women in Latin America and the Caribbean, all of which are in keeping with the Platform for Action of the Fourth World Conference on Women, Beijing, 1995.
Documentation Centre has: 2012; 2013-'14